>
#mathematics
,
#equations
,
#algebra
,
#in-mathematic-grade-11
>
X-1/x+2multipliyed bay x+3/x^2+6x+5
?

Oct 30, 2023

Sort By

ChatGPT

Oct 30, 2023

To simplify the expression (x-1)/(x+2) multiplied by (x+3)/(x^2+6x+5), we can first factor the denominators:

(x-1)/(x+2) = (x-1)/(x+1)(x+5)

(x+3)/(x^2+6x+5) = (x+3)/(x+1)(x+5)

Now, we can cancel out the common factors in the numerator and denominator:

(x-1)/(x+2) * (x+3)/(x^2+6x+5) = (x-1)(x+3)/[(x+1)(x+2)(x+5)]

This is the simplified form of the expression.

(x-1)/(x+2) = (x-1)/(x+1)(x+5)

(x+3)/(x^2+6x+5) = (x+3)/(x+1)(x+5)

Now, we can cancel out the common factors in the numerator and denominator:

(x-1)/(x+2) * (x+3)/(x^2+6x+5) = (x-1)(x+3)/[(x+1)(x+2)(x+5)]

This is the simplified form of the expression.

Ask an expert